2018
DOI: 10.1200/jco.2018.36.5_suppl.40
|View full text |Cite
|
Sign up to set email alerts
|

Cancer immunotherapy using trabectedin and nivolumab in advanced soft tissue sarcoma: A retrospective analysis.

Abstract: 40 Background: To restore innate tumor surveillance that is lost in cancer patients, a tumoricidal agent may have synergistic activity with an immune checkpoint inhibitor. Herein, we report on a retrospective analysis of our clinical experience using trabectedin, an alkylating agent, and nivolumab, a PD-1 inhibitor in advanced soft tissue sarcoma. Methods: Twenty previously treated STS patients received trabectedin (1.5 mg/m2 continuous intravenous infusion, CIV, for 24 hours) every 3 weeks, and nivolumab (3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Our group is currently developing a trial of doxorubicin plus dual CTLA‐4/PD‐1 blockade. A previously reported retrospective review of one center's experience with trabectedin plus pembrolizumab reported a favorable safety profile and preliminary evidence of efficacy . However, a previous trial of cyclophosphamide with pembrolizumab, intended to target tumor‐associated macrophages and T regs in addition to checkpoint blockade, showed disappointing results with no objective responses in cohorts of HGUPS and leiomyosarcoma subtypes .…”
Section: Sarcomas—a Framework For Approaching Modern Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Our group is currently developing a trial of doxorubicin plus dual CTLA‐4/PD‐1 blockade. A previously reported retrospective review of one center's experience with trabectedin plus pembrolizumab reported a favorable safety profile and preliminary evidence of efficacy . However, a previous trial of cyclophosphamide with pembrolizumab, intended to target tumor‐associated macrophages and T regs in addition to checkpoint blockade, showed disappointing results with no objective responses in cohorts of HGUPS and leiomyosarcoma subtypes .…”
Section: Sarcomas—a Framework For Approaching Modern Immunotherapymentioning
confidence: 99%
“…A previously reported retrospective review of one center's experience with trabectedin plus pembrolizumab reported a favorable safety profile and preliminary evidence of efficacy. 47 However, a previous trial of cyclophosphamide with pembrolizumab, intended to target tumor-associated macrophages and T regs in addition to checkpoint blockade, showed disappointing results with no objective responses in cohorts of HGUPS and leiomyosarcoma subtypes. 48 While these outcomes were not surprising for leiomyosarcoma, which has been shown to have an extremely low response rate to PD-1 monotherapy, 49,50 four of ten patients with HGUPS included in a study of pembrolizumab monotherapy had shown objective response.…”
Section: Cytotoxic Chemotherapymentioning
confidence: 99%
“… 48 Furthermore, a retrospective analysis with nivolumab and trabectedin in advanced STS demonstrated safety and efficiency of this combination against sarcoma. 49 Wagner et al. combined trabectedin with avelumab against advanced LMS and LPS.…”
Section: Resultsmentioning
confidence: 99%
“…These findings may be instructive when placed in the context of presently accessible treatment options for individuals with untreated MSTS [ 16 ]. The classic treatment for MSTS tends to be based on cytotoxic chemotherapy, with first-line therapy predictably accomplishing objective responses in 15–18% of individuals, with a median PFS of 4–6 months [ 7 , 17 ]. Activity beyond the first-line options tends to decline, with less than 10% of individuals reaching objective responses and a median PFS of 1–4 months [ 18 ].…”
Section: Discussionmentioning
confidence: 99%